-3(X-2)²+(X-5)(X+5)-2X(X-6)=?VA ROG FRUMOS
Răspunsuri la întrebare
Răspuns de
1
-3(x la a doua-4x+4)+x la a doua -25-2x la a doua +12x
-3x la a doua+12x-12+x la a doua-25-2 x la a doua+12
-4 x la doua+12 x-35
-3x la a doua+12x-12+x la a doua-25-2 x la a doua+12
-4 x la doua+12 x-35
Răspuns de
1
= -3(x^2 - 4x + 4) + x^2 - 25 - 2x^2 + 12x =
= -3x^2 + 12x - 12 + x^2 - 25 - 2x^2 + 12x =
= -4x^2 + 24x - 37
= -3x^2 + 12x - 12 + x^2 - 25 - 2x^2 + 12x =
= -4x^2 + 24x - 37
Alte întrebări interesante
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Engleza,
9 ani în urmă
Informatică,
10 ani în urmă
Matematică,
10 ani în urmă